An Exploratory Study of Spiritual Care at the End of Life - Daaleman, Timothy P. (American Academy of Family Physicians, 2008)
PURPOSE Although spiritual care is a core element of palliative care, it remains unclear how this care is perceived and delivered at the end of life. We explored how clinicians and other health care workers understand and view spiritual care provided to dying patients and their family members. METHODS Our study was based on qualitative research using key informant interviews and editing analysis with 12 clinicians and other health care workers nominated as spiritual caregivers by dying patients and their family members. RESULTS Being present was a predominant theme, marked by physical proximity and intentionality, or the deliberate ideation and purposeful action of providing care that went beyond medical treatment. Opening eyes was the process by which caregivers became aware of their patient’s life course and the individualized experience of their patient’s current illness. Participants also described another course of action, which we termed cocreating, that was a mutual and fluid activity between patients, family members, and caregivers. Cocreating began with an affirmation of the patient’s life experience and led to the generation of a wholistic care plan that focused on maintaining the patient’s humanity and dignity. Time was both a facilitator and inhibitor of effective spiritual care. CONCLUSIONS Clinicians and other health care workers consider spiritual care at the end of life as a series of highly fluid interpersonal processes in the context of mutually recognized human values and experiences, rather than a set of prescribed and proscribed roles.